Kirunafestivalen : En omvärldsanalys- och upplevelseproduktionsbaserad konceptutveckling - Hortlund, Jenny; Johansson, Frida (2013)
The festival industry is a major contributor to tourism in Sweden, which attracts thousands of visitors to cities around Sweden every year. However, in order to stand out in the ever-expanding industry, a festival is required to have an image and something unique to attract visitors. Kirunafestivalen wanted us to help them strengthen their position to stand out amongst all other festivals in Sweden. Therefore, we have with theories from experience production and an environmental scanning, developed a concept to strengthen the position of Kirunafestivalen and also its image. In order to provide information to the essay we; conducted a literature review, trend watched on the internet, a SWOT analysis as well as we have been in contact with the organizers of Kirunafestivalen and Åsa Stocksén and Gunnar Karlsson, who both after many years in the industry have a good understanding of trends and development prospects. The purpose with this festival is answered with a concept development that we consider will be necessary to create a clear image and strengthen their position among other festivals. The concept development assumes an environmental friendly and sustainable approach, where we let Kirunas indigenous people and their traditions to be in focus in order to take advantage of what is unique to Kiruna and to create a clear differentiation. Validerat; 20130708 (global_studentproject_submitter)